Regulatory protection of Asian elephants in Peninsular Malaysia and Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) - Lee, Ee Ling; Ariffin, Mariani; Abd Manaf, Latifah (International Organization Of Scientific Research, 2015)
Asian elephant is categorised as „endangered‟ in the IUCN Red List of Threatened Species of March 2015 and listed in Appendix I of Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) since July 1, 1975. In Malaysia, International Trade in Endangered Species Act 2008 (Act 686), hereinafter as “INTESA” is being enforced to regulate wildlife trade as required by CITES. Nevertheless, occurrences of illegal ivory trade and transit across Malaysia still happen even after the implementation of INTESA. Thus, the study is to determine the obligations of CITES in relation to Asian elephant conservation and to what extent INTESA addresses the obligations through inductive and deductive thematic content analysis method. The convention text, decisions and resolutions from CITES between 2004 and 2014 were gathered and analysed. Obligations and sub-obligations related to Asian elephant conservation were selected and categorised into themes and subthemes inductively to form a checklist. INTESA was read and analysed against the checklist to examine to what extent INTESA addresses the obligations of CITES. The study found that INTESA addresses elephant trade, including transit through systems of permit and certificate, yet, amendments in terms of import permit, definition of derivatives for ivory, regulation on ivory in transit, management of ivory stockpiles and elephant trades‟ records are imperative to protect Asian elephant from unlawful trade as outlined by CITES.